Introduction to microeconomics - "Laidler, David" (New Delhi, 1981)
An extensively re-writtten and re organised edition of this highly suc cessful text. The contents have now been arranged in shorter sections for ease of reference and revision. The theory of the firm chapters and those on welfare economics have been thoroughly revised and exten ded. As before, the book presents a modern treatment of microeconomics for serious students and is supple menfed by study questions and sug gestions for further reading. The mathematical techniques are kept as simple as possible and are virtually all goemetric.
Keywords: International coopertion